A Comparative Analysis of Government Systems: A Theoretical Study of Presidential, Parliamentary, and Indonesia’s Sui Generis Constitutional Dialectic Systems - Ogi Pracoyo; Reza Anggara Bahar; Yovan Iristian (Lex Journal: Kajian Hukum & Keadilan, 2026)
This research examines the complex dynamics of global governance models through a comparative lens, focusing on the fundamental dichotomy between presidential and parliamentary systems and the unique constitutional evolution of Indonesia. The primary objective is to analyze the structural efficacy, accountability mechanisms, and stability profiles of these systems in the context of contemporary democratic challenges such as the rise of populism and institutional erosion. Utilizing a normative juridical and comparative qualitative methodology, the study synthesizes constitutional provisions, recent Scopus-indexed literature (2020-2025), and landmark judicial decisions to provide an expert-level evaluation of institutional design. The findings reveal that while parliamentary systems excel in representativeness and collective responsibility through executive-legislative fusion, they often struggle with coalition instability. Conversely, presidential systems offer executive stability through fixed tenure but face risks of polarization, gridlock, and power concentration. Indonesia's system is identified as a "sui generis" model—a product of constitutional dialectics that attempts to purify the presidential executive while operating within a hyper-pluralistic multi-party environment. The research highlights the pivotal role of the Indonesian Constitutional Court in shifting the national priority from "governability" to "representativeness" through Decision No. 62/PUU-XXII/2024. The study concludes that the effectiveness of a government system is inherently tied to its cultural and historical context, requiring continuous institutional engineering to balance executive power with democratic inclusivity.